Characterization of the TRPV6 calcium channel-specific phenotype by RNA-seq in castration-resistant human prostate cancer cells - Cordier, Clément; Haustrate, Aurélien; Prevarskaya, Natalia; Lehen’kyi, V’yacheslav (Frontiers in Genetics, 2023)
Background: A highly calcium-selective channel TRPV6 has been shown to play a significant role in calcium homeostasis and to participate both in vitro and in vivo in growth, cell survival and drugresistance of the prostate cancer. Its role and the corresponding calcium-dependent pathways were mainly studied in hormone-dependent human prostate cancer cell lines, often used as a model of an early-stage prostate cancers. The goal of the present study was to describe the TRPV6-specific phenotype and signaling pathways it is involved in, using castration-resistant prostate cancer cell lines.Methods: RNA sequencing (RNA-seq) was used to study the gene expression impacted by TRPV6 using PC3M trpv6-/-versus PC3M trpv6+/+ and its derivative PC3M-luc-C6 trpv6+/+ cell line in its native and TRPV6 over-expressed form. In addition to the whole cell RNA sequencing, immunoblotting, quantitative PCR and calcium imaging were used to validate trpv6 gene status and functional consequences, in both trpv6 -/-and TRPV6 overexpression cell lines.Results: trpv6 -/-status was validated using both immunoblotting and quantitative PCR as well as the functional consequences of either trpv6 gene deletion or TRPV6 overexpression were shown using calcium imaging. RNA-seq analysis demonstrated that calcium channel TRPV6, being a crucial player of calcium-signaling, significantly impacts the expression of genes involved in cancer progression, such as cell cycle regulation, chemotaxis, migration, invasion, apoptosis, ferroptosis as well as drug resistance and extracellular matrix (ECM) re-organization.Our data suggest trpv6 gene is involved in and regulates multiple pathways related to the tumor progression and drug resistance in castration-resistant prostate cancer cells.